Migraciones estéticas en el primer teatro modernizador argentino: Henri-René Lenormand - Roberto Arlt - Grisby Ogás Puga (Les Cahiers ALHIM)
This article employs a comparative lens to analyze the migration of the Lenormandian dramatic model in the work of Roberto Arlt: one of Argentina’s key modern playwrights responsible for introducing changes and innovations that helped pave the way for the theatrical neovanguardia that erupted in Argentina during the sixties. We conceive of Roberto Arlt as an example of modern deterritorialization.  Perhaps due to his self-imposed marginalization with respect to Argentina’s political and intellectual scene, predominant literary trends and forms of language, Arlt was able to produce what we call ‘a dramaturgy of migrations’. With the resemanticization of the Lenormandian model and its superrealist and psychological elements, Arlt attempted to distance himself from the realist-naturalist, nativist-costumbrista aesthetic, in addition to the sainete and the sainete-influenced comedy. In this way he was able to transgress the national model with selective and productive incorporation of new poetics of the avantgarde through the rich aesthetic migrations that traversed the invisible borders of his theatre.